Mycetoma - Fahal, Ahmed Hassan (Henry Stewart Talks, 2021)
Mycetoma is a neglected tropical disease, Characteristics of mycetoma, The causative agents of mycetoma, The route of infection of mycetoma, Susceptibility to mycetoma, Clinical presentation, Diagnosing mycetoma, The late-presentation and poor management of mycetoma, Treating mycetoma including amputation